PHYTOCHEMICAL STUDIES OF Acacia catechu - Baluja, Shipra; Chanda, Sumitra; Solanki, Asif; Kachhadia, Nikunj (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2012)
Acacia catechu Willd. belongs to the family Mimosaceae. It is well known for the powder of wood known as Kathha” in India, which has wide applications. In the present work, the dry wood powder is extracted in various solvents such as 1,4-dioxane, methanol, dimethyl formamide (DMF), acetone, ethanol and distilled water. The phytochemical and physicochemical properties of these various solvent extracts were studied. The phyto constituents present in the different extracts were saponins, tannins, sugars, terpenes, catechu-tannic acid. Alkaloids were present in organic solvents only. The antibacterial activity of all the extracts in DMSO was studied against five bacterial strains but none of the extracts inhibit any of the studied bacterial strains.Key words: Acacia catechu, 1,4-dioxane, methanol, dimethyl formamide (DMF), acetone, ethanol, distilled water, phytochemical analysis, physicochemical analysis.